On prediction and filtering problem of long-run stationary time series - Cau, Phan Dang (Journal of Computer Science and Cybernetics, 2016)
Suppose by the  irregularity of the reflectivity of the earth a seismic signal is not always stationary in usual sense, but only long-run stationary (see [6,7]). Then  there arises a question: ‘why is wiener filter, which is  as well known is used in prediction and filtering of ergodic stationary time series, also applicable in processing seismic signals? In this paper we try to give answer to this question.